ANALISIS PENERAPAN PSAP NO. 07 TENTANG AKUNTANSI ASET TETAP PADA KANTOR BADAN DIKLAT PEMERINTAH PROVINSI SULAWESI UTARA - Engka, Fresly Kornelius; Tinangon, Jantje J.; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Statement of Government Accounting Standards (PSAP) 07 is the standard for the accounting of fixed assets include the recognition, the determination of the carrying value, the accounting treatment of the revaluation and impairment of the carrying (carrying value) of fixed assets. Fixed assets have a very important role and should be managed well in order to produce reliable information in the financial statements. This study aims to determine the suitability of adoption of a PSAP 07 on fixed asset accounting in the Kantor Badan DIKLAT Provinsi Sulawesi Utara. The method used is descriptive analysis method. The results showed Badan DIKLAT in the application of accounting of fixed assets, namely the classification, recognition, measurement / assessment, depreciation record, expenses after the acquisition, termination and release, as well as the disclosure is in accordance with the PSAP 07,Â  but is need to know,Â  Badan DIKLAT use SIMDA application to record the depreciation fixed asset.Keywords : Aplication, Analysis, PSAP 07, Fixed Asset